Efeito de diferentes níveis de bicarbonato de sódio em dietas com bagaço de cana-de-açúcar auto-hidrolisado sobre a degradação in situ do milho e farelo de algodão - Bergamaschine, A. F.; de Andrade, P.; Malheiros, E. B. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1997)
The objective of this work was to evaluate the buffering effect of sodium bicarbonate (NaHCO3), used in the levels of: 0, 0.7, 1.4 and 2.1% of dry matter, on the in situ degradation of corn and cottonseed meal. A diet with 60% autohidrolised sugar bagasse (BAH) and 40% of concentrate was used, plus urea, minerals and limestone. The rations was calculated to allow 300g of daily gain. After 20 days of adaptation to the treatment (levels of NaHCO3), 5g of each feed was incubated in the rumen of four bovines for 3, 6, 12, 24 and 48 hours, using naylon bag with size of 7,5 x 17,5 cm with pores of 36 micras. A randomized blocks design with four treatment (levels of NaHCO3) were used. The buffer affected the in situ dry matter degradation, whose means were 49.68; 63,10; 67,71; and 60,85% and 25.89; 30.88; 33.48 and; 31.02% for the corn and cottonseed meal, respectively. The level of 1.4% of NaHCO3 provided the highest value of degradability, which did not differ from the 0.7% and 2.1% levels, for the corn. The degradability of protein was not affected by the treatments.
Effects of different levels of sodium bicarbonate in diet with autohydrolised sugar-cane bagasse on in situ degradability of the corn and cottonseed meal
Keywords: autohydrolised sugar-cane bagasse; sodium bicarbonate; in situ degradation; cottonseed meal; corn